Efektivitas Penggunaan Multimedia Presentasi dalam Meningkatkan Ketertarikan Siswa Terhadap Bahasa Arab di Satit Phatnawitya Yala School Thailand - Yuki Ramadhani Panggabean; Mavianti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research examines whether multimedia presentations increase Arabic interest at Satit Phatnawitya Yala School Thailand. This is descriptive qualitative study. All primary school kids at Darusslam were sampled. This research found that multimedia presentations engage students and decrease boredom in online and offline learning. Future multimedia development demands mass media innovation to boost student quality and comprehension.